Analysis of Building Permit Processing Delays Using Fishbone Diagram, 5 Why-Why Analysis, and 5W+1H Method - Putra, Agus Jerry Suarjana; Nusraningrum, Dewi (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: The objective of this study is to analyze the impact of implementing structured quality management tools, specifically the Fishbone Diagram, Why-Why Analysis, and 5W + 1H method, on reducing project permit processing delays in the construction industry, with a focus on improving efficiency at the transportation industry.Methodology: This study uses a qualitative research approach, collecting data through interviews, document analysis, and direct observations within the transportation industry. The Fishbone Diagram, Why-Why Analysis, and 5W + 1H method were systematically applied to identify the root causes of permit processing delays and take strategic steps so that permit delays do not occur again.Finding: The findings reveal that the application of these structured quality management tools significantly reduces permit processing delays by improving coordination between authorities to obtain approval for additional time, supported by clear progress reports and justifications for the causes of delays.Conclusion: The study concludes that the integration of the Fishbone Diagram, Why-Why Analysis, and 5W + 1H methods in the permit processing workflow effectively addresses operational inefficiencies. Future research should expand on these findings by applying these methods across different companies and regions to improve the management of Building Construction permits so that the Company avoids losses due to project cost overruns.